Acid Attacks in India and the Role of Stakeholders: A Journey From Victim to Survivor - Rashida Salmani; Geeta Mishra
With the increase in acid-related violence in India, vitriolage has become one of the most gruesome forms of hate crimes to be conceived and committed. This crime was majorly associated with being one of the most heinous atrocities against women. Still, in recent times, it has been observed that acid attacks are not gender specific anymore. This study set out to determine the reasons why people use acid, as well as the difficulties that assault victims face. It also recommends actions taken to address such issues and the involvement of all parties engaged in rehabilitating acid attack survivors while considering gender. The researcher followed a multiple case study approach, conducted thorough semi-structured interviews of 22 acid attack survivors and used secondary data sources. We found that acid attacks happen out of jealousy, anger, greed and ego issues, among other causes, and that it is not a gender-specific crime. Stakeholders greatly help in adopting strategies and measures that facilitate acid attack survivors.